Calculation of the damage area in anticorrosion coating of the pipeline section according to the data of electric measurements - V. V. Lukovich; Yu. G. Kalkutin (Геофизический журнал, 2012)
A mathematical model, an algorithm and a program are developed. They allow the computation of damage area of pipeline anti-corrosion coating, the polarization potential and the current density in a damage using electrometric measurement data. The computation of corresponding parameters from these data was carried out.